Coastal Forest vegetation of Sabutung Island South Sulawesi - Dody Priosambodo (Universitas Hasanuddin, 2018)
Research about coastal forest vegetation in Sabutung island has been conducted.The aim of this research was to make an inventory of native species, introduced speciesand invasive spesies of plant in Sabutungisland. Sampling activities conducted withpurposive sampling method.Data collected with noted the plant species that foundduring exploring the island. All sample are photographed. Unidentified sample werecollected and identified in Marine and Environmental laboratory, Department ofBiology, Faculty of Mathematics and Natural Sciences, Hasanuddin University.Identification of the sample conducted based on: An Annotated Check-List of TheVascular Plants of The South China Sea and Its Shores by Turner et al. (2000) and Mangrove Guidebook for Southeast Asia by Wim Giesen et al. (2007)for coastal forestspecies; Tropical flowering plants: a guide to identification and cultivation by KirstenAlbrecht Llamas (2003) for introduced species andNonnative Invasive Plants of PacificCoast Forest. A Field Guide for Identification oleh Gray et al. (2011) and Guide to TheNaturalized and Invasive Plants of Southeast Asia by Arne Witt (2017) for invasivespecies. Data were analysed descriptively and displayed in tabular form. Antropogenicimpact i.e: land conversion and increased population were also discussed. From theresults of the study were recorded as many as 221 species of plants in Sabutung Island.Mostly dominated by ornamental plants and cultivated (introduced) plants with 131species of 46 tribes followed by native species with 67 species from 34 tribes. Invasivespecies were recorded with at least 19 species from 8 tribes. Nonetheless, invasivespecies are widespread and dominate space in almost all parts of the island. Most of thecoastal forest on Sabutung Island has been lost due to land conversion to settlementsand garden/plantation.